Bioassay Screening of the Essential Oil and Various Extracts of Nigella sativa L. Seeds Using Brine Shrimp Toxicity Assay - Fariba Sharififar; Ali Assadipour; Mohammad Hassan Moshafi; Fahimeh Alishahi; Hossein Mahmoudvand* (Lorestan University of Medical Sciences, 2017)
Background and Aim: Since cytotoxicity screening is the first step necessary for any new drug development, this study was designed to find out and compare the cytotoxicity effects of the essential oil and various extracts of Nigella sativa L. seeds using Brine Shrimp Lethality (BSL) assay. Materials and Methods: Essential oils and various extracts of N. sativa were assessed by two methods of disk and solution of BSL. Data analysis was carried out using SPSS statistical package version 17.0 (SPSS Inc., Chicago, IL, 250 USA). Data were processed in probit-analysis program to estimate LC50 values. Results: All of the tested fractions demonstrated more cytotoxicity in the solution method. Petroleum ether and chloroform extract of N. sativa showed the most cytotoxicity with LC50 values 7 and 21 μg/ml respectively; while aqueous and ethanolic had no significant cytotoxicity. Moreover, the GC/MS analysis of the essential oil of N. sativa showed the p-cymene (48.1%), α-thujone (14.38%) and dihydro carveol (9.11%) as the main compounds. Conclusion: These results suggest some limitation for using this spice in diet. Furthermore, this plant could be considered as a source of cytotoxic compounds which should be studied in details.